Twelve tips for providing feedback to peers about their teaching. (3rd October 2019) - Newman, Lori R.; Roberts, David H.; Frankl, Susan E.
Abstract: When healthcare professionals provide feedback to peers after a teaching observation, there are benefits for both parties. In this article, we outline strategies to use before, during, and after teaching observations to engage in mutually-beneficial conversations that highlight best practices, identify solutions for teaching dilemmas, and initiate teaching relationships. We discuss the importance of choosing words wisely; giving feedback about teaching skills, not the teacher as a person; recognizing how colleagues view their teaching identities; and ensuring peers are emotionally ready for a post-observation conversation. We also explain how to use pronouns, questions, and active listening during feedback conversations. Finally, we explore the impact of biases on observations, how to establish peer observer credibility, and how to make the teaching observation process and feedback discussion valuable experiences for both parties so that it leads to long-lasting partnerships in the quest to improve educational quality.